Isolating membrane slurry, isolating membrane, battery and electric device
By adding mesoporous ceramic particles to the isolation film to adsorb transition metal ions, the problem of impaired battery circulation performance and energy density is solved, higher circulation performance and energy density is achieved, and the infiltration rate of the electrolyte is improved.
Patent Information
- Application Number
- CN202310942596.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-28
- Publication Date
- 2025-02-14
AI Technical Summary
During the charging and discharging process of existing batteries, transition metal ions are easily precipitated from the electrode material, diffuse to the anode and destroy the SEI film, affecting the cycling performance and energy density of the battery.
Mesoporous ceramic particles are added to the isolation film, and the transition metal ions are adsorbed using the specific surface area of the mesoporous to reduce the damage of the positive electrode material and the dissolution of the transition metal ions, thereby reducing the damage to the negative electrode SEI film and improving the cycling performance of the battery.
By adsorbing transition metal ions, the damage to the positive and negative electrodes is reduced, and the cycle performance and energy density of the battery are significantly improved, while the infiltration rate of the electrolyte is increased, further improving the performance of the battery cell.
Smart Images

Figure CN119447695A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to an isolation membrane slurry, an isolation membrane, a battery and an electrical device. Background Art
[0002] In order to improve the rate performance and cycle performance of the battery, various metals and transition metal materials are used in electrode active materials. During the charge and discharge process, transition metal ions are easily precipitated from the electrode materials and diffused to the anode, which will destroy the SEI film, affect the cycle performance of the battery, and reduce the energy density of the battery. Summary of the invention
[0003] The present application is made in view of the above-mentioned problems, and its purpose is to provide a separator slurry to adsorb transition metal ions and improve the cycle performance of the battery.
[0004] In order to achieve the above-mentioned objectives, the embodiments of the present application provide an isolation membrane slurry, an isolation membrane, a battery and an electrical device.
[0005] In a first aspect, an embodiment of the present application proposes an isolation membrane slurry, comprising ceramic particles, a binder and a solvent, wherein the ceramic particles at least include mesoporous ceramic particles.
[0006] Therefore, in the technical solution of the embodiment of the present application, by adding mesoporous ceramic particles to the separator, the specific surface area of the mesopores is utilized to adsorb transition metal ions, reduce the damage to the positive electrode material, and reduce the dissolution and migration of transition metal ions to the negative electrode, thereby reducing the damage to the negative electrode SEI film and improving the cycle performance of the battery. In addition, the mesoporous ceramic particles have a large specific surface area, which can also increase the infiltration rate of the electrolyte, further improving the performance of the battery cell.
[0007] It should be noted that the mesoporous ceramic particles may be conventional isolation membrane ceramic particles, such as at least one of Al2O3, SiO2, MgO, CaO, ZrO2 and TiO2.
[0008] In any embodiment, in the mesoporous ceramic particles, the pore size of the mesopores is d1, 5nm≤d1≤100nm, the pore size of the mesopores affects the adsorption of transition metal ions, and the adsorption effect is better within the range of 5nm to 100nm. Optionally, 10nm≤d1≤40nm, within this range, the effect of transition metal adsorption is better.
[0009] It should be noted that the pore size of the mesopores may be an average pore size or a median pore size.
[0010] In any embodiment, the specific surface area of the mesoporous ceramic particles is S, 20m 2 / g≤S≤500m 2 / g, the specific surface area of mesoporous ceramic particles affects the adsorption of transition metal ions. 2 / g, it can have a good adsorption effect, and at the same time can improve the dispersion performance of the slurry, so that the mesoporous ceramic particles are evenly dispersed in the isolation membrane, thereby evenly adsorbing transition metal ions. Optionally, 80m 2 / g≤S≤200m 2 / g, within this range, the adsorption effect of transition metals is better.
[0011] In any embodiment, the particle size of the mesoporous ceramic particles is d2, 50nm≤d2≤500nm, the particle size of the mesoporous ceramic particles affects the adsorption of transition metal ions, and a better adsorption effect can be achieved within the range of 50nm to 500nm. Optionally, 100nm≤d2≤350nm, within this range, the effect of transition metal adsorption is better. It should be noted that the particle size of the mesoporous ceramic particles is the Dv50 value.
[0012] In any embodiment, the mesoporous ceramic particles include at least one of mesoporous TiO2 and mesoporous Al2O3. TiO2 and Al2O3 are conventional separator ceramic particle materials, which will not introduce new compounds and reduce the impact on the battery's electrical performance. At the same time, these two materials are cheap and easy to obtain, which can reduce costs. It is particularly important to note that when the mesoporous ceramic particles include mesoporous TiO2, the polarity of TiO2 can be further utilized to improve the adsorption of transition metal ions, thereby further improving the battery's cycle performance.
[0013] In any embodiment, the mass proportion of mesoporous ceramic particles in the isolation membrane slurry is w1, 1%≤w1≤30%, and the mass proportion of mesoporous ceramic particles in the isolation membrane slurry affects the effect of transition metal adsorption and the conduction of conductive ions. When w1 is between 1% and 30%, the probability of mesoporous ceramic particles agglomerating to form gel in the isolation membrane slurry is low, reducing the impact on the barrier properties of the isolation membrane, while taking into account the adsorption of transition metal ions and improving the cycle performance of the battery. Optionally, 5%≤w1≤20%, within this range, the effect of transition metal adsorption is better.
[0014] In any embodiment, the solid content in the isolation membrane slurry is w2, and the solid content in the isolation membrane slurry is the content of solid particles in the isolation membrane. The solid particles in the isolation membrane include mesoporous ceramic particles and ordinary ceramic particles. 30%≤w2≤90%. Within this range, the solid particle content in the isolation membrane is appropriate. While ensuring the barrier performance, the isolation membrane slurry has appropriate viscosity, good fluidity, easy coating, and good adsorption performance for transition metals. Optionally, 50%≤w2≤70%. Within this range, the effect of transition metal adsorption is better.
[0015] In any embodiment, the binder includes at least one of polyvinylidene fluoride, styrene-butadiene rubber and sodium carboxymethyl cellulose. Adopting at least one of the above binders can improve the bonding performance of the isolation film slurry; and / or,
[0016] The solvent includes at least one of N-methylpyrrolidone and water. Using at least one of the above solvents can improve the volatility of the solvent and reduce the cost.
[0017] In a second aspect, an embodiment of the present application provides an isolation film, comprising:
[0018] basement membrane; and
[0019] The mesoporous isolation membrane coating is arranged on at least one side of the base membrane, and the material of the mesoporous isolation membrane coating at least includes mesoporous ceramic particles.
[0020] By providing a mesoporous isolation membrane coating on at least one side of the base membrane, an isolation membrane containing mesoporous ceramic particles can be obtained, which improves the adsorption of transition metal ions, improves the cycle performance of the battery, and reduces the damage of transition metal ions to the negative electrode SEI membrane.
[0021] In any embodiment, the mesoporous isolation membrane coating is provided on both sides of the base membrane. By providing the mesoporous isolation membrane coating on both sides of the base membrane, the adsorption of transition metal ions can be further improved, the cycle performance of the battery can be improved, and the damage of transition metal ions to the negative electrode SEI membrane can be reduced.
[0022] In any embodiment, in the mesoporous ceramic particles, the pore size of the mesopores is d1, 5nm≤d1≤100nm, the pore size of the mesopores affects the adsorption of transition metal ions, and the adsorption effect is better within the range of 5nm to 100nm. Optionally, 10nm≤d1≤40nm, within this range, the effect of transition metal adsorption is better. And / or,
[0023] The specific surface area of the mesoporous ceramic particles is S, 20m 2 / g≤S≤500m 2 / g, the specific surface area of mesoporous ceramic particles affects the adsorption of transition metal ions. 2 / g, it can have a good adsorption effect, and at the same time can improve the dispersion performance of the slurry, so that the mesoporous ceramic particles are evenly dispersed in the isolation membrane, thereby evenly adsorbing transition metal ions. Optionally, 80m 2 / g≤S≤200m 2 / g, within this range, the effect of transition metal adsorption is better. And / or,
[0024] In any embodiment, the particle size of the mesoporous ceramic particles is d2, 50nm≤d2≤500nm, the particle size of the mesoporous ceramic particles affects the adsorption of transition metal ions, and a better adsorption effect can be achieved within the range of 50nm to 500nm. Optionally, 100nm≤d2≤350nm, within this range, the effect of transition metal adsorption is better. It should be noted that the particle size of the mesoporous ceramic particles is the Dv50 value. And / or,
[0025] The mesoporous ceramic particles include at least one of mesoporous TiO2 and mesoporous Al2O3. TiO2 and Al2O3 are conventional separator ceramic particle materials, which will not introduce new compounds and reduce the impact on the battery's electrical performance. At the same time, these two materials are cheap and easy to obtain, which can reduce costs. It is particularly important to note that when the mesoporous ceramic particles include mesoporous TiO2, the polarity of TiO2 can be further utilized to improve the adsorption of transition metal ions, thereby further improving the battery's cycle performance.
[0026] In any embodiment, the thickness of the mesoporous isolation membrane coating is 0.5 to 30 nm. The thickness of the mesoporous isolation membrane coating affects the isolation performance and ion conduction performance. In the range of 0.5 to 30 nm, the isolation membrane can have good isolation effect and lithium dendrite piercing performance, maintain suitable interface impedance, and maintain a suitable lithium ion transmission path length to improve ion conduction performance and battery kinetics performance, while taking into account the adsorption of transition metal ions; optionally, the thickness of the mesoporous isolation membrane coating is 1 to 20 nm. Within this range, the isolation performance and adsorption performance are better.
[0027] In a third aspect, an embodiment of the present application provides a battery, comprising a positive electrode, a negative electrode, and the isolation membrane of the second aspect of the present application.
[0028] In any embodiment, at least one side of the base membrane facing the positive electrode is provided with the mesoporous isolation membrane coating. At least one side of the base membrane facing the positive electrode is provided with the mesoporous isolation membrane coating, that is, it may contain only one mesoporous isolation membrane layer, and the mesoporous isolation membrane layer faces the positive electrode, or it may contain two mesoporous isolation membrane layers, one side facing the positive electrode and the other side facing the negative electrode. When it contains only one mesoporous isolation membrane layer, and the mesoporous isolation membrane layer faces the positive electrode, the transition metal ions can be adsorbed between the positive electrode and the diaphragm, and their diffusion to the anode surface to destroy the SEI film of the anode is inhibited. By providing the mesoporous isolation membrane coating on at least one side of the base membrane facing the positive electrode, the mesoporous isolation membrane coating in contact with the positive electrode can effectively adsorb transition metals, improve the adsorption rate, and thus improve the cycle performance of the battery.
[0029] In any embodiment, the battery is a primary battery or a secondary battery.
[0030] In a fourth aspect, an embodiment of the present application provides an electrical device, comprising the battery of the fourth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 is a schematic structural diagram of an isolation membrane according to an embodiment of the present application;
[0032] Figure 2 is a schematic structural diagram of an isolation membrane according to an embodiment of the present application;
[0033] Figure 3 is a schematic structural diagram of an isolation membrane according to an embodiment of the present application;
[0034] Figure 4 Schematic diagram of a secondary battery according to one embodiment of the present application.
[0035] Figure 5 yes Figure 1 An exploded view of a secondary battery according to an embodiment of the present application is shown.
[0036] Figure 6 is a schematic diagram of a battery module according to an embodiment of the present application.
[0037] Figure 7 It is a schematic diagram of a battery pack according to one embodiment of the present application.
[0038] Figure 8 yes Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown.
[0039] Fig. 9 Schematic diagram of an electrical device using a secondary battery according to an embodiment of the present application as a power source.
[0040] Description of reference numerals:
[0041] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 top cover assembly; 521 isolation membrane; 5211 base membrane; 5212 mesoporous isolation membrane coating; 5213 isolation membrane coating DETAILED DESCRIPTION
[0042] The following specifically discloses the embodiments of the separator slurry, separator, battery and electric device of the present application. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0043] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0044] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0045] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0046] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0047] In order to improve the rate performance and cycle performance of the battery, various metals and transition metal materials are used in electrode active materials. During the charge and discharge process, transition metal ions are easily precipitated from the electrode materials and diffused to the anode, which will destroy the SEI film, affect the cycle performance of the battery, and reduce the energy density of the battery.
[0048] Therefore, there are endless studies on transition metal adsorption, for example, a positive electrode material, a positive electrode, a preparation method, a method for inhibiting cation dissolution and a lithium ion battery, wherein the positive electrode material includes a positive electrode active substance and an additive, wherein the additive includes a nano-TiO2 / carbon composite material, wherein the nano-TiO2 / carbon composite material includes a carbon carrier and nano-TiO2 loaded on the carbon carrier, and wherein the nano-TiO2 has mesopores. The present invention adopts a nano-TiO2 / carbon composite material, and adds a trace amount of the composite material to the positive electrode, which can significantly inhibit the dissolution of cations in the positive electrode and improve the cycle performance and safety performance of the battery. However, in the above scheme, the addition of the mesoporous TiO2 / carbon composite material to the positive electrode can easily lead to gelation of the slurry during the preparation of the slurry due to its mesoporous structure, causing the battery performance to deteriorate; in addition, after being added to the positive electrode, the proportion of the positive electrode active substance will be reduced, thereby reducing the energy density of the battery.
[0049] Unexpectedly, by adding mesoporous ceramic particles to the separator slurry of the separator, the formation of gel of the separator slurry can be reduced, while reducing the squeezing of the positive electrode active material, achieving the effect of adsorbing transition metal ions and improving the cycle performance of the battery.
[0050] Based on this, the present application provides an isolation membrane slurry, an isolation membrane, a battery and an electrical device.
[0051] In a first aspect, an embodiment of the present application proposes an isolation membrane slurry, comprising ceramic particles, a binder and a solvent, wherein the ceramic particles at least include mesoporous ceramic particles.
[0052] Therefore, in the technical solution of the embodiment of the present application, by adding mesoporous ceramic particles to the separator, the specific surface area of the mesopores is utilized to adsorb transition metal ions, reduce the damage to the positive electrode material, and reduce the dissolution and migration of transition metal ions to the negative electrode, thereby reducing the damage to the negative electrode SEI film and improving the cycle performance of the battery. In addition, the mesoporous ceramic particles have a large specific surface area, which can also increase the infiltration rate of the electrolyte, further improving the performance of the battery cell.
[0053] It should be noted that the mesoporous ceramic particles may be conventional isolation membrane ceramic particles, such as at least one of Al2O3, SiO2, MgO, CaO, ZrO2 and TiO2.
[0054] In any embodiment, in the mesoporous ceramic particles, the pore size of the mesopores is d1, 5nm≤d1≤100nm, and the pore size of the mesopores affects the adsorption of transition metal ions. In the range of 5nm to 100nm, the adsorption effect is better. The pore size can be 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm or 100nm. Optionally, 10nm≤d1≤40nm, within this range, the effect of transition metal adsorption is better. It should be noted that the pore size of the mesopores can be an average pore size or a median pore size, wherein the average pore size can be measured in the following manner:
[0055]
[0056] Total pore volume: also known as total pore volume, is the amount of vapor adsorbed when the relative pressure is close to 1;
[0057] The total pore volume has a well-known meaning in the art, and this parameter is calculated based on a pore size distribution differential diagram, which can be measured using instruments and methods well-known in the art, for example, reference can be made to the national standard GB / T 19587-2017 "Determination of the specific surface area of solid substances by gas adsorption BET method".
[0058] In any embodiment, the specific surface area of the mesoporous ceramic particles is S, 20m 2 / g≤S≤500m 2 / g, the specific surface area of mesoporous ceramic particles affects the adsorption of transition metal ions. 2 / g, it can have a good adsorption effect, and at the same time can improve the dispersion performance of the slurry, so that the mesoporous ceramic particles are evenly dispersed in the isolation membrane, thereby evenly adsorbing transition metal ions. The specific surface area of the mesoporous ceramic particles can be 20m 2 / g, 60m 2 / g, 80m 2 / g, 120m 2 / g, 160m 2 / g, 200m 2 / g, 250m 2 / g、300m 2 / g, 350m 2 / g, 400m 2 / g, 450m 2 / g or 500m 2 / g. Optionally, 80m 2 / g≤S≤200m 2 / g, within this range, the effect of transition metal adsorption is better. It should be noted that the specific surface area BET is a well-known meaning in the art and can be measured using instruments and methods well-known in the art. For example, the national standard GB / T19587-2017 "Determination of the specific surface area of solid substances by gas adsorption BET method" can be referred to.
[0059] In any embodiment, the particle size of the mesoporous ceramic particles is d2, 50nm≤d2≤500nm, the particle size of the mesoporous ceramic particles affects the adsorption of transition metal ions, and a better adsorption effect can be achieved within the range of 50nm to 500nm. The particle size of the mesoporous ceramic particles can be 50nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm or 500nm. Optionally, 100nm≤d2≤350nm, within this range, the effect of transition metal adsorption is better. It should be noted that the particle size of the mesoporous ceramic particles is the Dv50 value. It should be noted that the particle size value has a well-known meaning in the art and can be measured using instruments and methods well-known in the art. For example, the particle size distribution-laser diffraction method can be used, and the test operation refers to GB / T19077-2016 ("Particle Size Distribution Laser Diffraction Method". Pages 4-10)
[0060] In any embodiment, the mesoporous ceramic particles include at least one of mesoporous TiO2 and mesoporous Al2O3. TiO2 and Al2O3 are conventional separator ceramic particle materials, which will not introduce new compounds and reduce the impact on the battery's electrical performance. At the same time, these two materials are cheap and easy to obtain, which can reduce costs. It is particularly important to note that when the mesoporous ceramic particles include mesoporous TiO2, the polarity of TiO2 can be further utilized to improve the adsorption of transition metal ions, thereby further improving the battery's cycle performance.
[0061] In any embodiment, the mass proportion of mesoporous ceramic particles in the isolation membrane slurry is w1, 1%≤w1≤30%, and the mass proportion of mesoporous ceramic particles in the isolation membrane slurry affects the effect of transition metal adsorption and the conduction of conductive ions. When w1 is between 1% and 30%, the probability of mesoporous ceramic particles agglomerating to form gel in the isolation membrane slurry is low, reducing the impact on the barrier properties of the isolation membrane, while taking into account the adsorption of transition metal ions and improving the cycle performance of the battery. The mass proportion of mesoporous ceramic particles in the isolation membrane slurry can be 1%, 3%, 5%, 10%, 15%, 20%, 25% or 30%. Optionally, 5%≤w1≤20%, within this range, the effect of transition metal adsorption is better.
[0062] In any embodiment, the solid content in the isolation membrane slurry is w2, and the solid content in the isolation membrane slurry is the content of solid particles in the isolation membrane. The solid particles in the isolation membrane include mesoporous ceramic particles and ordinary ceramic particles, 30%≤w2≤90%. Within this range, the solid particle content in the isolation membrane is appropriate. While ensuring the barrier performance, the isolation membrane slurry has appropriate viscosity, good fluidity, easy coating, and good adsorption performance for transition metals. The solid content in the isolation membrane slurry can be 30%, 40%, 50%, 60%, 70%, 80% or 90%; optionally, 50%≤w2≤70%. Within this range, the effect of transition metal adsorption is better.
[0063] In any embodiment, the binder includes at least one of polyvinylidene fluoride, styrene-butadiene rubber and sodium carboxymethyl cellulose. Adopting at least one of the above binders can improve the bonding performance of the isolation film slurry; and / or,
[0064] The solvent includes at least one of N-methylpyrrolidone and water. Using at least one of the above solvents can improve the volatility of the solvent and reduce the cost.
[0065] Second, as Figures 1 to 3 As shown, the embodiment of the present application provides an isolation film 521, including:
[0066] base film 5211; and
[0067] The mesoporous isolation film coating 5212 is disposed on at least one side of the base film 5211 , and the material of the mesoporous isolation film coating 5212 at least includes mesoporous ceramic particles.
[0068] By providing a mesoporous isolation membrane coating 5212 on at least one side of the base membrane 5211, an isolation membrane 521 containing mesoporous ceramic particles can be obtained, thereby improving the adsorption of transition metal ions, improving the cycle performance of the battery, and reducing the damage of transition metal ions to the negative electrode SEI membrane.
[0069] In any embodiment, if Figure 1 As shown, the mesoporous isolation membrane coating 5212 is provided on both sides of the base membrane 5211. By providing the mesoporous isolation membrane coating 5212 on both sides of the base membrane 5211, the adsorption of transition metal ions can be further improved, the cycle performance of the battery can be improved, and the damage of transition metal ions to the negative electrode SEI film can be reduced.
[0070] In any embodiment, if Figure 2 As shown, one side of the base film 5211 is provided with the mesoporous isolation film coating 5212 , and the other side is provided with a conventional ceramic coating 5213 .
[0071] In any embodiment, if Figure 3As shown, one side of the base film 5211 is provided with the mesoporous isolation film coating 5212, and the other side is not provided with the coating.
[0072] In any embodiment, in the mesoporous ceramic particles, the pore size of the mesopores is d1, 5nm≤d1≤100nm, the pore size of the mesopores affects the adsorption of transition metal ions, and the adsorption effect is better in the range of 5nm to 100nm. The pore size can be 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm or 100nm. Optionally, 10nm≤d1≤40nm, within this range, the effect of transition metal adsorption is better; and / or,
[0073] The specific surface area of the mesoporous ceramic particles is S, 20m 2 / g≤S≤500m 2 / g, the specific surface area of mesoporous ceramic particles affects the adsorption of transition metal ions. 2 / g, it can have a good adsorption effect, and at the same time can improve the dispersion performance of the slurry, so that the mesoporous ceramic particles are evenly dispersed in the isolation membrane, thereby evenly adsorbing transition metal ions. Optionally, 80m 2 / g≤S≤200m 2 / g, within this range, the effect of transition metal adsorption is better. The specific surface area of mesoporous ceramic particles can be 20m 2 / g, 60m 2 / g, 80m 2 / g, 120m 2 / g, 160m 2 / g, 200m 2 / g, 250m 2 / g、300m 2 / g, 350m 2 / g, 400m 2 / g, 450m 2 / g or 500m 2 / g. Optionally, 80m 2 / g≤S≤200m 2 / g, within this range, the adsorption effect of transition metals is better; and / or,
[0074] The particle size of the mesoporous ceramic particles is d2, 50nm≤d2≤500nm. The particle size of the mesoporous ceramic particles affects the adsorption of transition metal ions, and a better adsorption effect can be achieved within the range of 50nm to 500nm. The particle size can be 50nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm or 500nm. Optionally, 100nm≤d2≤350nm, within this range, the effect of transition metal adsorption is better. It should be noted that the particle size of the mesoporous ceramic particles is the Dv50 value. And / or,
[0075] The mesoporous ceramic particles include at least one of mesoporous TiO2 and mesoporous Al2O3. TiO2 and Al2O3 are conventional separator ceramic particle materials, which will not introduce new compounds and reduce the impact on the battery's electrical performance. At the same time, these two materials are cheap and easy to obtain, which can reduce costs. It is particularly important to note that when the mesoporous ceramic particles include mesoporous TiO2, the polarity of TiO2 can be further utilized to improve the adsorption of transition metal ions, thereby further improving the battery's cycle performance.
[0076] In any embodiment, the thickness of the mesoporous isolation membrane coating 5212 is 0.5-30 nm. The thickness of the mesoporous isolation membrane coating 5212 affects the isolation performance and ion conductivity performance. In the range of 0.5-30 nm, the isolation membrane can have a good isolation effect, improve the ion conductivity performance, and take into account the adsorption of transition metal ions. Optionally, the thickness of the mesoporous isolation membrane coating 5212 is 1-20 nm. Within this range, the isolation performance and adsorption performance are better.
[0077] In a third aspect, an embodiment of the present application provides a battery, comprising a positive electrode, a negative electrode, and the isolation membrane of the second aspect of the present application.
[0078] In any embodiment, at least one side of the base membrane facing the positive electrode is provided with the mesoporous isolation membrane coating. At least one side of the base membrane facing the positive electrode is provided with the mesoporous isolation membrane coating, that is, it may contain only one mesoporous isolation membrane layer, and the mesoporous isolation membrane layer faces the positive electrode, or it may contain two mesoporous isolation membrane layers, one side facing the positive electrode and the other side facing the negative electrode. When it contains only one mesoporous isolation membrane layer, and the mesoporous isolation membrane layer faces the positive electrode, the transition metal ions can be adsorbed between the positive electrode and the diaphragm, and their diffusion to the anode surface to destroy the SEI film of the anode is inhibited. By providing the mesoporous isolation membrane coating on at least one side of the base membrane facing the positive electrode, the mesoporous isolation membrane coating in contact with the positive electrode can effectively adsorb transition metals, improve the adsorption rate, and thus improve the cycle performance of the battery.
[0079] In any embodiment, the battery is a primary battery or a secondary battery.
[0080] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0081] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes the positive electrode active material of the first aspect of the present application.
[0082] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0083] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0084] In some embodiments, when the secondary battery is a lithium-ion battery, the positive electrode active material may adopt a positive electrode active material for lithium-ion batteries that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0085] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0086] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0087] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0088] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0089] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0090] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0091] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0092] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0093] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0094] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0095] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0096] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0097] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0098] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0099] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0100] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0101] In some embodiments, the material of the isolation membrane base film can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane base film can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane base film is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0102] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0103] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0104] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0105] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 4 The secondary battery 5 is a square structure as an example.
[0106] In some embodiments, reference Figure 5 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0107] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0108] Figure 3 4 is an example of a battery module. Figure 6 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.
[0109] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0110] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0111] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 7 and Figure 8 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0112] In a fourth aspect, an embodiment of the present application provides an electrical device, comprising the battery of the third aspect of the present application.
[0113] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited to these.
[0114] As the electrical device, a secondary battery, a battery module or a battery pack may be selected according to its usage requirements.
[0115] Fig. 9 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the power consumption device's requirements for high power and high energy density of secondary batteries, a battery pack or a battery module can be used.
[0116] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.
[0117] Example
[0118] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0119] The parameters of the isolation film slurries of Examples 1 to 23 of the present application and Comparative Examples 1 to 2 are as shown in Table 1.
[0120]
[0121] Embodiment 24
[0122] A release film, wherein both sides of a base film have a release film coating prepared from the release film slurry of Example 23.
[0123] Embodiment 25
[0124] A release film, wherein one side of a base film has a release film coating prepared from the release film slurry of Example 23.
[0125] Embodiment 26
[0126] An isolation membrane, wherein one side of a base membrane has an isolation membrane coating prepared from the isolation membrane slurry of Example 23, and the other side has a conventional isolation membrane ceramic coating.
[0127] Embodiment 27
[0128] A battery, wherein the separator coating on the side close to the positive electrode is a separator prepared from the separator slurry of Example 23, and the side close to the negative electrode is a conventional ceramic separator coating.
[0129] Embodiment 28
[0130] A battery, wherein the separator coating on the side close to the positive electrode is the separator coating prepared from the separator slurry of Example 23.
[0131] Embodiment 29
[0132] A battery, wherein the isolation membrane coatings on the side close to the positive electrode and the side close to the negative electrode are both isolation membrane coatings prepared from the isolation membrane slurry of Example 23.
[0133] Embodiment 30
[0134] A battery, wherein the separator coating on the side close to the negative electrode is the separator coating prepared from the separator slurry of Example 23, and there is no separator coating on the side close to the positive electrode.
[0135] Performance Testing
[0136] The separator slurries of Examples 1 to 23 and Comparative Examples 1 to 2 were prepared into separators, and the separators of Examples 24 to 26 were stacked in a vacuum glove box in the order of positive electrode shell-positive electrode sheet-electrolyte-diaphragm-negative electrode sheet-negative electrode shell, and the positive electrode sheet, separator, and negative electrode sheet were assembled into a full battery in sequence, and the batteries of Examples 27 to 30 were tested as follows:
[0137] Electrical performance test
[0138] Cycle performance test: 1C constant current charging to 4.3V, constant voltage charging to 0.05C, discharge 1C constant current discharge to 2.5V; perform charge and discharge cycles, and record the cycle retention rate when the battery cycle decays to 80% SOH.
[0139] The statistical experimental results are shown in Tables 1 and 2.
[0140] Table 2 Performance parameters of Examples 24 to 30
[0141] The number of cycles when the battery cycle decays to 80% SOH Embodiment 24 2662 Embodiment 25 2523 Embodiment 26 2547 Embodiment 27 2613 Embodiment 28 2599 Embodiment 29 2662 Embodiment 30 2557
[0142] As can be seen from Table 1, through Examples 1 to 4 and Comparative Examples 1 to 2, it can be seen that by adding mesoporous ceramic particles to the separator, the specific surface area of the mesopores is utilized to adsorb transition metal ions, reduce the damage to the positive electrode material, and reduce the dissolution and migration of transition metal ions to the negative electrode, thereby reducing the damage to the negative electrode SEI film and improving the cycle performance of the battery. Comparative Example 1 does not add mesoporous ceramic particles, and Comparative Example 2 mesoporous ceramic particles are added to the positive electrode slurry. The cycle performance of Examples 1 to 3 is better than that of Comparative Example 1 and Comparative Example 2.
[0143] It can be seen from Examples 5 to 10 that the pore size of the mesopores affects the adsorption of transition metal ions, and the adsorption effect is better in the range of 5nm to 100nm. 10nm≤d1≤40nm, the effect of transition metal adsorption is better, and the cycle performance of the battery is better.
[0144] From Examples 11 to 16, it can be seen that the particle size of mesoporous ceramic particles affects the adsorption of transition metal ions, and a better adsorption effect can be achieved in the range of 50nm to 500nm. When 100nm≤d2≤350nm, the effect of transition metal adsorption is better and the cycle performance of the battery is better.
[0145] It can be seen from Examples 17 to 23 that the mass proportion of mesoporous ceramic particles in the separator slurry affects the effect of transition metal adsorption and the conduction of conductive ions. When w1 is between 1% and 30%, the probability of mesoporous ceramic particles agglomerating to form gel in the separator slurry is low, reducing the impact on the barrier properties of the separator, while taking into account the adsorption of transition metal ions and improving the cycle performance of the battery. In the range of 5% ≤ w1 ≤ 20%, the effect of transition metal adsorption is better, further improving the cycle performance of the battery.
[0146] It can be seen from Examples 24 to 30 that when there is only one mesoporous isolation film layer and the mesoporous isolation film layer faces the positive electrode, the transition metal ions can be adsorbed between the positive electrode and the separator, and their diffusion to the anode surface to destroy the SEI film of the anode can be inhibited. By providing the mesoporous isolation film coating on at least one side of the base film facing the positive electrode, the mesoporous isolation film coating in contact with the positive electrode can effectively adsorb transition metals, increase the adsorption rate, and thus improve the cycle performance of the battery. The effect is better when the mesoporous isolation film coating is provided on both sides.
[0147] In summary, in the separator slurry proposed in the present application, by adding mesoporous ceramic particles to the separator, the specific surface area of the mesopores is utilized to adsorb transition metal ions, reduce the damage to the positive electrode material, and reduce the dissolution and migration of transition metal ions to the negative electrode, thereby reducing the damage to the negative electrode SEI film and improving the cycle performance of the battery. In addition, the mesoporous ceramic particles have a large specific surface area, which can also increase the infiltration rate of the electrolyte and further improve the performance of the battery cell.
[0148] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A separator slurry, characterized in that: The invention comprises ceramic particles, a binder and a solvent, wherein the ceramic particles at least comprise mesoporous ceramic particles.
2. The isolation film slurry according to claim 1, characterized in that: In the mesoporous ceramic particles, the pore size of the mesopores is d1, 5nm≤d1≤100nm, optionally, 10nm≤d1≤40nm.
3. The isolation film slurry according to claim 1 or 2, characterized in that: The specific surface area of the mesoporous ceramic particles is S, 20m 2 / g≤S≤500m 2 / g, optionally, 80m 2 / g≤S≤200m 2 / g.
4. The isolation film slurry according to any one of claims 1 to 3, characterized in that: The particle size of the mesoporous ceramic particles is d2, 50nm≤d2≤500nm, optionally, 100nm≤d2≤350nm.
5. The isolation film slurry according to any one of claims 1 to 4, characterized in that: The mesoporous ceramic particles include at least one of Al2O3 and TiO2.
6. The isolation film slurry according to any one of claims 1 to 5, characterized in that: The mass proportion of the mesoporous ceramic particles in the isolation membrane slurry is w1, 1%≤w1≤30%; optionally, 5%≤w1≤20%.
7. The isolation film slurry according to any one of claims 1 to 6, characterized in that: The solid content in the isolation membrane slurry is w2, 30%≤w2≤90%; optionally, 50%≤w2≤70%.
8. The isolation film slurry according to any one of claims 1 to 7, characterized in that: The binder comprises at least one of polyvinylidene fluoride, styrene-butadiene rubber and sodium carboxymethyl cellulose; and / or, The solvent includes at least one of N-methylpyrrolidone and water.
9. A separation film, characterized in that: include: Basement membrane; as well as, The mesoporous isolation membrane coating is arranged on at least one side of the base membrane, and the material of the mesoporous isolation membrane coating at least includes mesoporous ceramic particles.
10. The isolation film according to claim 9, characterized in that The mesoporous isolation film coating is disposed on both sides of the base film.
11. The isolation film according to claim 9 or 10, characterized in that: In the mesoporous ceramic particles, the pore size of the mesopores is d1, 5nm≤d1≤100nm, optionally, 10nm≤d1≤40nm; and / or, The specific surface area of the mesoporous ceramic particles is S, 20m2 / g≤S≤500m2 / g, optionally, 80m2 / g 2 / g≤S≤200m 2 / g; and / or, The particle size of the mesoporous ceramic particles is d2, 50nm≤d2≤500nm, optionally, 100nm≤d2≤350nm; and / or, The mesoporous ceramic particles include at least one of Al2O3 and TiO2.
12. The isolation film according to any one of claims 9 to 11, characterized in that: The thickness of the mesoporous isolation membrane coating is 0.5-30 nm; optionally, the thickness of the mesoporous isolation membrane coating is 1-20 nm.
13. A battery, characterized in that: include: positive electrode; negative electrode; as well as The isolation membrane according to any one of claims 9 to 12.
14. The battery according to claim 13, characterized in that At least one side of the base film facing the positive electrode is provided with the mesoporous isolation film coating.
15. An electrical device, characterized in that: Comprising a battery as claimed in claim 13 or 14.
Citation Information
Patent Citations
Method for surface ceramic-coating of lithium-ion battery separator
CN103311485A
Lithium battery comprising composite flame retardant particles
CN114649498A
Secondary battery, battery module, battery pack, and electric device
CN116231092A